Ensuring The Safe Movement of Vehicles on Mountain Roads (Eurasian Scientific Herald, 2023)
This article discusses the features of traffic on mountainous sections of roads in the conditions of the Republic of Uzbekistan, analyzes the intensity and composition of traffic flows, features of road conditions, traffic accidents